Israel, the Palestinian factions, and the cycle of violence - David A. Jaeger; Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2006)
In this study we extend our previous work to examine the dynamic relationship between violence committed by Palestinian factions and that committed by Israel during the Second Intifada. We find a statistically significant relationship between Israeli fatalities claimed by groups associated with the ruling political party, Fatah, and subsequent Palestinian fatalities. We do not find a similar relationship for Israeli fatalities claimed by Hamas, Palestinian Islamic Jihad, and other Palestinian factions. We conjecture that these differences are due to the different positions of the factions vis-à-vis bargaining over a two-state solution to the conflict as well as the organizational structures of the factions.
Keywords: 330; Intifada; terrorism; conflict resolution; bargaining; violence; Politische Gewalt; Israel; Palästina; Politische Gewalt; Israel; Palästina